Approach and Methods on TEFL: Inquiry-Based Language Learning (IBLL) - Rejeki, Sri (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2017)
This paper aims at explaining the theoretical based and the implementation of Inquiry-Based Language Learning particularly in Indonesia. IBLL is not quite familiar in Indonesian context especially in educational field. In other hand, Curriculum 2013 is very popular in this country although both of them are related each other. This curriculum adopted the concept of IBLL in which it encourages the students to construct the knowledge. Based on the principle of inquiry, the students supported by the teacher and peers try to answer the questions coming from themselves. These answers will help them in constructing the knowledge. IBLL is completely useful in promoting long life education that enables them to continue the quest for knowledge throughout life.